Numerical Simulation and Experiment of the Effects of Blade Angle Deviation on the Hydraulic Characteristics and Pressure Pulsation of an Axial-Flow Pump - Lijian Shi; Jun Zhu; Yao Yuan; Fangping Tang; Penglan Huang; Wenpeng Zhang; Haiyu Liu; Xiaowen Zhang (Shock and Vibration)
Inadequate blade angle adjustment or manufacturing errors will cause inconsistencies in the blade angle of an axial-flow pump. In this study, the hydrodynamic characteristics of an axial-flow pump with inconsistent blade angle are investigated by analyzing hydraulic performance and pressure pulsation. The analysis is conducted by performing a numerical simulation combined with a model test. Results show that, relative to the case without blade angle deviation, the case with blade angle deviation exhibits changes in the periodicity of the flow field in the impeller. Such changes result in uneven pressure changes in the impeller passage. The pressure pulsation induced by the blade angle deviation is mainly low-frequency pulsation; that is, it is twice the rotation frequency. The amplitude of the main frequency pulsation is 1.5–3 times that of the blade without angle deviation. This low frequency that dominates the whole pump device easily causes the vibration and weakens the safety and stability of the pump. The blade angle deviation exerts great influence on the unsteady characteristics. Hence, blade angle deviation seriously affects the safe and stable operation of axial-flow pumps and pump stations.